Plant‐derived protein bodies as delivery vehicles for recombinant proteins into mammalian cells. Issue 4 (30th January 2020) - Schwestka, Jennifer; Tschofen, Marc; Vogt, Stefan; Marcel, Sylvain; Grillari, Johannes; Raith, Marianne; Swoboda, Ines; Stoger, Eva
Abstract: The encapsulation of biopharmaceuticals into micro‐ or nanoparticles is a strategy frequently used to prevent degradation or to achieve the slow release of therapeutics and vaccines. Protein bodies (PBs), which occur naturally as storage organelles in seeds, can be used as such carrier vehicles. The fusion of the N‐terminal sequence of the maize storage protein, γ‐zein, to other proteins is sufficient to induce the formation of PBs, which can be used to bioencapsulate recombinant proteins directly in the plant production host. In addition, the immunostimulatory effects of zein have been reported, which are advantageous for vaccine delivery. However, little is known about the interaction between zein PBs and mammalian cells. To better understand this interaction, fluorescent PBs, resulting from the fusion of the N‐terminal portion of zein to a green fluorescent protein, was produced in Nicotiana benthamiana leaves, recovered by a filtration‐based downstream procedure, and used to investigate their internalization efficiency into mammalian cells. We show that fluorescent PBs were efficiently internalized into intestinal epithelial cells and antigen‐presenting cells (APCs) at a higher rate than polystyrene beads of comparable size. Furthermore, we observed that PBs stimulated cytokine secretion by epithelial cells, a characteristic that may confer vaccine adjuvant activities through the recruitment of APCs. Taken together, these results support the use of zein fusion proteins in developing novel approaches for drug delivery based on controlled protein packaging into plant PBs. Abstract : In this study, the use of plant‐made protein bodies (PBs) for protein delivery into mammalian cells was explored. Fluorescent PBs produced in N. benthamiana leaves were recovered by a filtration‐based downstream procedure and incubated with human colon epithelial and macrophage‐like cells. PBs were internalized into mammalian cells at a higher rate than polystyrene beads of comparable size and stimulated cytokine secretion by epithelial cells. The findings support the development of zein‐based PBs as a drug delivery vehicle.